Assessment of microplastics and nanoplastics released from a chopping board using Raman imaging in combination with three algorithms - Luo, Yunlong; Chuah, Clarence; Amin, Md. Al; Khoshyan, Ashkan; Gibson, Christopher T.; Tang, Youhong; Naidu, Ravi; Fang, Cheng (Journal of hazardous materials, 2022)
As contaminants of emerging concern, microplastics and nanoplastics are ubiquitous in not only aquatic and terrestrial environments but also household settings. While the characterisation of microplastics is still a challenge, the analysis of nanoplastics is even more difficult. In this study, we aim to examine several novel algorithmic methods intended for analysing complex Raman spectrum matrices towards visualisation of plastic particles released from a chopping board. Specifically, we compare and advance three decoding algorithms, including (i) a logic-based algorithm to merge and cross-check multiple Raman images that map the intensities of several characteristic peaks; (ii) a principal component analysis-based algorithm to generate intensity images from whole sets of spectra, not just from individual characteristic peaks; (iii) an algebra-based algorithm to merge and cross-check the loading matrix to enhance characterisation efficiency. Assisted with a scanning electron microscope, we estimate that 100–300 microplastics / nanoplastics per mm per cut along the groove formed on the chopping board, and ~3000 per mm2 per cut in the scratched area, may be released from a chopping board during food preparation and may be subsequently ingested by human. Overall, the Raman imaging combined with algorithms can provide effective characterisation of microplastics and nanoplastics. [Display omitted] •Logic-/PCA-Raman imaging directly visualises microplastics and even nanoplastics.•Algebra-based algorithm can cross-check images to increase assignment certainty.•Algebra-based algorithm has calculation flexibility and enhance PCA algorithm.•Microplastics / nanoplastics may be released when using a plastic chopping board.•100–300 microplastics / nanoplastics are generated per mm per cut, or 3000 per mm2.